X-marks: Too simple to be useful? - Marquis, Raymond; Mazzella, Williams David; Hicks, Tacha (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
This paper presents a case illustrating the value that can be elicited from simple handwritten entries such as X-marks. An experimental study was carried out for the case needs, where X-marks were collected from a population of 52 writers and classified according to the stroke direction. To fulfil the recommendations of the ENFSI guideline on evaluative reporting in forensic science, the results of this study were used to quantitatively assess handedness of the writer of the questioned X-mark.
Keywords: znaki X; interpretacja kryminalistyczna; ocena dowodów; współczynnik prawdopodobieństwa